2022
DOI: 10.3390/cancers14205161
|View full text |Cite
|
Sign up to set email alerts
|

Higher Risk of Recurrence in Patients Treated for Head and Neck Cancer with Low BMI and Elevated Levels of C-Reactive Protein

Abstract: This prospective study identifies high-risk groups for recurrence of head and neck cancer by BMI and circulating inflammatory response markers. Head and neck cancer patients from three Swedish hospitals were included (n = 272). Leukocyte and thrombocyte counts, CRP levels, and BMI were measured pre-treatment and post-treatment. Associations between the four factors and treatment failure (residual tumor, loco-regional failure, general failure/distant metastasis) were assessed using a Cox proportional hazards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Another parameter, which is not always included in lab tests, and which is also a marker of a proinflammatory status, is the reactive C protein (RCP). Both of these parameters, are unspecific, which could justify why the studies have not reached a consensus on them [16,17,33].…”
Section: Peripheral Blood Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter, which is not always included in lab tests, and which is also a marker of a proinflammatory status, is the reactive C protein (RCP). Both of these parameters, are unspecific, which could justify why the studies have not reached a consensus on them [16,17,33].…”
Section: Peripheral Blood Leukocytesmentioning
confidence: 99%
“…Multiple authors have shown how patient variables such as age and comorbidities can influence outcomes [1,2]. But interestingly, there has been an increasing interest in using peripheral blood factors such as leukocytes, albumin or hemoglobin as surrogates of the host status in head and neck cancer patients [3–9,10 ▪▪ ,11 ▪▪ ,12,13 ▪▪ ,14–22]. Generally, these variables are gathered prior to treatment initiation.…”
Section: Introductionmentioning
confidence: 99%